Bimbingan Kelompok Bermuatan Nilai Kakawin Sutasoma untuk Mengelola Sikap Kebinekaan Global - Thadeus Ega Fausta; Muslihati Muslihati; Henny Indreswari (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The global diversity is one dimension of the Pancasila student profile. Upon further examination, the dimension of global diversity is closely related to the attitude of tolerance. However, tolerance cannot be ingrained in students on its own without assistance from others. Therefore, assistance from others is needed in managing the global diversity of students. The aim of this research is to examine guidance and counseling services that integrate Indonesian cultural values. This research uses the Systematic Literature Review (SLR) method. The results obtained include 14 articles that meet the study's objectives, with 5 articles relevant to global diversity, 5 articles relevant to guidance strategies in the era of independent learning, and 4 articles relevant to the values of Kakawin Sutasoma. The findings from this literature review suggest the possibility of guidance services infused with the values of Kakawin Sutasoma, as there is similarity between the aspects of global diversity and the verses in the Kakawin Sutasoma text. Further research is needed to design group guidance activities infused with the values of Kakawin Sutasoma to manage the global diversity attitudes of students.